1993
DOI: 10.1101/gad.7.8.1521
|View full text |Cite
|
Sign up to set email alerts
|

The nonspecific DNA-binding and -bending proteins HMG1 and HMG2 promote the assembly of complex nucleoprotein structures.

Abstract: The mammalian high mobility group proteins HMG1 and HMG2 are abundant, chromatin-associated proteins whose cellular function is not known. In this study we show that these proteins can substitute for the prokaryotic DNA-bending protein HU in promoting the assembly of the Hin invertasome, an intermediate structure in Hin-mediated site-specific DNA inversion. Formation of this complex requires the assembly of the Hin recombinase, the Fis protein, and three cis-acting DNA sites, necessitating the looping of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
327
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(340 citation statements)
references
References 89 publications
12
327
0
1
Order By: Relevance
“…They bind to the minor groove of DNA through a cluster of hydrophobic residues [32]. They may cover a long region of DNA through the formation of oligomers [33,34]. All these properties are consistent with specific binding to alternating AT clusters, in particular if they are unstabilized by torsional stress or cruciform formation: HMGB proteins always bind to distorted DNA regions.…”
Section: Homologue Chromosome Recognition In Meiosismentioning
confidence: 77%
See 1 more Smart Citation
“…They bind to the minor groove of DNA through a cluster of hydrophobic residues [32]. They may cover a long region of DNA through the formation of oligomers [33,34]. All these properties are consistent with specific binding to alternating AT clusters, in particular if they are unstabilized by torsional stress or cruciform formation: HMGB proteins always bind to distorted DNA regions.…”
Section: Homologue Chromosome Recognition In Meiosismentioning
confidence: 77%
“…Just as an eventual possibility, it can be mentioned that the Nhp6 proteins in yeast meet all the required properties. They may wrap around DNA duplexes [33] and have a preference for alternating AT sequences [30, Fig.4s]. They are present in the cell in sufficient amount and have multiple roles in chromosome structure and function [35].…”
Section: Homologue Chromosome Recognition In Meiosismentioning
confidence: 99%
“…62 HMGB proteins have been observed to aid the formation of DNA loop complexes, similarly to the role of HU. 63,64 To explain these results, a simple model allows random transient binding to DNA, inducing random kinks that serve to compact the overall DNA structure. 62,64 Alternatively, HMG proteins may bind (perhaps being even unable to dissociate), changing the flexibility, possibly by locally denaturing the DNA as seen in recent experiments on the E. coli.…”
Section: Protein Binding To the Double Helixmentioning
confidence: 99%
“…DNA compaction by enhanced apparent flexibility suggests one general activity of HMGB proteins in vivo: reducing the effective persistence length of bulk DNA [39]. Such an effect would be important for stabilizing highly strained or distorted DNA conformations such as are encountered in recombination [29]. We have recently shown that bacterial cells lacking the architectural DNA binding protein HU are significantly disabled in lac operon repression looping [40], and expression of ectopic HMGB proteins can partially substitute for HU [40].…”
mentioning
confidence: 99%
“…Studies by Johnson and co-workers [29] have shown that eukaryotic HMGB proteins can functionally replace bacterial architectural proteins in reconstituted in vitro recombination systems that require enhanced DNA bending. This and subsequent work [30;31;32;33;34;35; 36], suggests a model to explain how HMGB proteins enhance the rate of ligase-catalyzed DNA cyclization (Fig.…”
mentioning
confidence: 99%